2022
DOI: 10.3390/s22239109
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Quality Evaluation Using Connected Vehicle Data

Abstract: Modern vehicles have extensive instrumentation that can be used to actively assess the condition of infrastructure such as pavement markings, signs, and pavement smoothness. Currently, pavement condition evaluations are performed by state and federal officials typically using the industry standard of the International Roughness Index (IRI) or visual inspections. This paper looks at the use of on-board sensors integrated in Original Equipment Manufacturer (OEM) connected vehicles to obtain crowdsource estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…This can be especially important for high-traffic areas or areas that are prone to damage as it allows for quick and targeted interventions to prevent further deterioration. The use and validation of this data source are proposed in Mahlberg et al, 2022(Mahlberg et al, 2022b. Production vehicle data for pavement quality leverages individual wheel speed via rotational sensors in combination with drivetrain data to provide accurate roughness information (Magnusson and Svantesson, 2021).…”
Section: Data Opportunities and Motivationmentioning
confidence: 99%
“…This can be especially important for high-traffic areas or areas that are prone to damage as it allows for quick and targeted interventions to prevent further deterioration. The use and validation of this data source are proposed in Mahlberg et al, 2022(Mahlberg et al, 2022b. Production vehicle data for pavement quality leverages individual wheel speed via rotational sensors in combination with drivetrain data to provide accurate roughness information (Magnusson and Svantesson, 2021).…”
Section: Data Opportunities and Motivationmentioning
confidence: 99%
“…This data has already shown wide-ranging applicability to prioritize traffic signal retiming, monitor mobility in varying weather conditions, and assess work zone mobility [20,23,24]. Including additional probe, CV data sources provide unique opportunities to evaluate transportation infrastructure and prioritize investments, including pavement markings, pavement quality, and the deterioration of roadway conditions during winter storms using friction data [21,25]. Combining all of these emerging CV data attributes can provide stakeholders and planning commissions with a holistic view of the transportation network and present opportunities to invest in infrastructure improvements, including electric vehicle charging.…”
Section: Emerging Connected Vehicle Data Opportunitiesmentioning
confidence: 99%
“…Mahlberg et al ( 2022) argued that despite the lack of standards for using connected vehicles to monitor pavement quality, agencies can begin to benefit from its potential for network level monitoring [22]. The authors suggested that even non-connected modern vehicles have extensive instrumentation that agencies can leverage to monitor infrastructure condition including pavement markings, signs, and pavement smoothness.…”
Section: Connected Vehiclesmentioning
confidence: 99%